Inflammation and type 2 diabetes - Donath, Marc Y. (Henry Stewart Talks, 2013)
Mechanisms of insulin secretion defect in type 2 diabetes, Islet inflammation in type 2 diabetes, Role of IL-1beta and inflammasome in type 2 diabetes, Treatment of type 2 diabetes, IL-6 and GLP-1
Archived at 2022/02/27